Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1530/edm-14-0037
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related thyroiditis: a case report and review of literature

Abstract: SummaryA 55-year-old male, with a positive medical history for hypothyroidism, treated with stable doses for years was admitted with subacute thyroiditis and a feeling of pain and pressure in the neck. Laboratory tests showed decrease in TSH levels, elevated erythrocyte sedimentation rate, and very high antithyroid antibodies. Owing to enlarging goiter and exacerbation in the patient's complaints, he was operated with excision of a fibrotic and enlarged thyroid lobe. Elevated IgG4 plasma levels and high IgG4/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…The cytological findings of IgG4 thyroiditis are poorly documented, with rare reports in the literature describing features of lymphocytic thyroiditis, without additional details. 10,11 The cytological features in our case corroborate the histological findings. The prominent microfollicular distribution with Hurthle cell change may result in a false diagnosis of Hurthle cell neoplasm, as illustrated in our case.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The cytological findings of IgG4 thyroiditis are poorly documented, with rare reports in the literature describing features of lymphocytic thyroiditis, without additional details. 10,11 The cytological features in our case corroborate the histological findings. The prominent microfollicular distribution with Hurthle cell change may result in a false diagnosis of Hurthle cell neoplasm, as illustrated in our case.…”
Section: Discussionsupporting
confidence: 85%
“…The cytological findings of IgG4 thyroiditis are poorly documented, with rare reports in the literature describing features of lymphocytic thyroiditis, without additional details . The cytological features in our case corroborate the histological findings.…”
Section: Discussionsupporting
confidence: 78%
“…5 IgG4-RD is now considered a systemic disease that may affect various organs and that is characterized by progressively growing fibroinflammatory lesions causing mass effects. 6 Since its first description, 2 IgG4-related thyroiditis has been considered a subtype of Hashimoto's thyroiditis. 7 Its clinicopathologic features are similar to those of the fibrous variant of HT and Riedel's thyroiditis (RT), suggesting that IgG4-related HT is a type of fibrous variant of HT and RT.…”
Section: Discussionmentioning
confidence: 99%
“…Salook et al [14] reported a patient who presented with an acute elevation in T4 and suppressed TSH associated with neck pain. The patient had already been diagnosed with Hashimoto's thyroiditis and was on a stable dose of thyroxine.…”
Section: Igg4-related Disorders and The Thyroidmentioning
confidence: 99%